Effectivness of genicular nerves radiofrequency neuroablation for pain syndrome managment in patients with knee arthritis - Golovakha, M. L.; Bilykh, Y. O.; Головаха, Максим Леонідович; Білих, Євген Олегович (My University, 2020)
Abstract. Most people in age above 65 years with knee arthritis suffer from pain syndrome. Traditionally, this pain is nociceptive and an important part of knee osteoarthritis treatment is pain management. Radiofrequency neuroablation was proposed as a long-term and effective method of the pain syndrome treatment that inducts the nociceptive mechanism in the structures that conduct pain impulses. Objectives: analyze the effectiveness of pain syndrome treatment with radiofrequency neuroablation in patients with knee arthritis for 6 months after the procedure.
Keywords: pain syndrome; knee osteoarthritis; radiofrequency neuroablation